Tempering the taste for vengeance: Information about prisoners and policy choices in Chile - Carlos G. Scartascini; Fernando G. Cafferata; Daniel W. Gingerich (Inter-American Development Bank (IDB), 2020)
Punitive anti-crime policies in the Americas have contributed to steadily increasing rates of incarceration. This creates prison overcrowding and can lead to recidivism. Harsh penalties are often demanded by citizens, making them politically attractive for politicians. Yet the contextual determinants of participation in crime are rarely understood by the public. In this paper, we employ a survey experiment conducted in Chile in order to examine how the provision of information about the prison population shapes tastes for punitive anti-crime policies. Respondents in the treatment group received information about the low educational attainment of prisoners. This information led to substantial changes in policy preferences. Tasked with allocating resources to anti-crime policies using a fixed budget, treated respondents assigned between 20% to 50% more to socially oriented anti-crime policies (relative to punitive policies) than respondents in the control group, and they reduced their support for 'iron fist' policing. This indicates that providing information to citizens might change the policy equilibrium in the Americas.
Keywords: D91; D78; H42; K14; 330; Survey experiments; Information; Beliefs; Crime; Public Policy